2022
DOI: 10.3389/fendo.2022.874291
|View full text |Cite
|
Sign up to set email alerts
|

RJX Improves Wound Healing in Diabetic Rats

Abstract: BackgroundWe recently reported the clinical safety profile of RJX, a well-defined intravenous GMP-grade pharmaceutical formulation of anti-oxidant and anti-inflammatory vitamins as active ingredients, in a Phase 1 study in healthy volunteers (ClinicalTrials.gov Identifier: NCT03680105) (Uckun et al., Front. Pharmacol. 11, 594321. 10.3389/fphar.2020.594321). The primary objective of the present study was to examine the effects of GMP-grade RJX on wound and burn injury healing in diabetic rats.MethodsIn the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Although process of epithelialization was complete in the A6B8-treated group, fibroblast and collagen regeneration were also more evident in the A6B8-treated group, with properly arranged bundles sited parallel to the newly formed epidermis in comparison with the A0B8- and A8B0-treated groups. 77…”
Section: Resultsmentioning
confidence: 99%
“…Although process of epithelialization was complete in the A6B8-treated group, fibroblast and collagen regeneration were also more evident in the A6B8-treated group, with properly arranged bundles sited parallel to the newly formed epidermis in comparison with the A0B8- and A8B0-treated groups. 77…”
Section: Resultsmentioning
confidence: 99%
“…In general, during the wound healing process, re-epithelialization begins after the formation of granulation tissue at the wound site [ 31 ]. However, because wound healing mechanism is inhibited in diabetic mice, re-epithelialization in diabetic mice is prolonged compared with that in normal mice [ 32 ]. In our study, α-SMA-positive cells (myofibroblasts) were identified after POD 9 in granulation tissue of the artificial-AM group.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of HFD and low‐dose STZ is widely used to establish the type 2 diabetes model in rats (Sahin et al, 2019 ; Uckun et al, 2022 ; Wickramasinghe et al, 2022 ). Excessive fat intake elevated serum and liver FFA may promote inflammatory hepatic damage and insulin resistance (Ma et al, 2018 ), leading to the deterioration of glucose metabolism and subsequent hyperglycemia, hyperinsulinemia, and dyslipidemia (Sahin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis model assessment of insulin resistance (HOMA‐IR) was detected, as stated by Uckun et al ( 2022 ). The average fasting blood glucose levels (4.38 mmol/L) and insulin (10.63 mIU/L) were detected, and the coefficient was computed as 46.52.…”
Section: Methodsmentioning
confidence: 99%